Uterine collision tumor (PEComa and endometrioid carcinoma) in a tuberous sclerosis patient: a case report - Koufopoulos, Nektarios; Pateras, Ioannis S.; Koratzanis, Christos; Gouloumis, Alina-Roxani; Ieronimaki, Argyro-Ioanna; Fotiou, Alexandros; Panayiotides, Ioannis G.; Vrachnis, Nikolaos (Frontiers in Oncology, 2023)
Perivascular epithelioid cell tumors are very rare mesenchymal neoplasms arising in various locations, such as the female genital tract, kidney, lung, prostate, bladder, pancreas, soft tissues, and bone. They possess a unique immunophenotype, co-expressing myogenic and melanocytic markers; molecular findings include mutations of tuberous sclerosis complex and translocations of transcription factor E3, a member of the microphthalmia transcription factor gene family. We herewith report a uterine collision tumor consisting of a perivascular epithelioid cell tumor and a moderately differentiated endometrial endometrioid carcinoma in a patient with genetically proven tuberous sclerosis; two leiomyomas were also found in contact with the tumor. Although two such cases one with a benign and another with a malignant perivascular epithelioid cell tumor have previously been reported, ours is, to our knowledge, the first reported in a tuberous sclerosis patient.